Isodimorphic aliphatic copolyester as midblock of poly(l-lactide)-based triblock copolymers towards largely enhanced impact toughness. (February 2019) - Zhang, Bufeng; Wei, Zhiyong; Zhao, Yabiao; Che, Rui; Wang, Yanshai; Leng, Xuefei; Li, Yang
Graphical abstract: Highlights: Biobased biodegradable ABA type triblock copolyesters have been successfully synthesized. An eutectic copolyester as soft midblock towards high impact strength of 357.2 J/m. A new green path for increase toughness of PLLA by incorporation of flexible aliphatic polyester. Abstract: Biobased dihydroxy-terminated aliphatic copolyesters were synthesized from melt-polycondensation of 1, 6-adipic acid with 1, 6-hexanediol and 1, 10-decanediol. The isodimorphic behavior of the copolyesters was explored to identify the pseudo-eutectic copolyester, which was selected as macro-initiator for ring opening polymerization ofl -lactide to prepare poly(l -lactide)-b-poly(hexamethylene-co-decamethylene adipate)-b-poly(l -lactide) (PLLA-b-PHDA-b-PLLA) triblock copolymers varying PLLA block length. The blocky structure was confirmed by GPC and NMR, and the influence of PLLA block length on physical and mechanical properties was investigated. Impact testing showed that the impressive impact strength was achieved, that is, the values of PLLA10-PHDA-PLLA10 and PLLA20-PHDA-PLLA20 were largely enhanced to 357.2 J/m and 259.6 J/m, respectively, about 9–12 times greater than that of PLLA homopolymer (28.6 J/m). SEM micrographs of impact fractured surface showed that the triblock copolymers underwent a transition from brittle fracture of neat PLLA to ductile fracture, which is attributed to the introduction of flexible aliphatic polyester as middle soft building block of triblcok copolymers. This work demonstrated isodimorphic aliphatic copolyesters as midblock of PLLA-based triblock fully biobased biodegradable copolymers towards highly toughened PLLA material.